Respostas

A melhor resposta!
2014-01-14T11:40:03-02:00
O problema tem mais de uma solução pois não sabemos qual é o par de lados iguais.

1° caso: AB = BC
BC² = (-1-5)² + (4- (-2))² = 72
AB² = (x - (-1))² + (6 - 4)² = (x+1)² + 4

Igualando teremos: (x+1)² + 4 = 72 ----> (x+1)² = 68 ----> x = -1+2√17 ou x = -1-2√17

2° caso: AB = AC
AB² = (x+1)² + 4
AC² = (x-5)² + (6-(-2))² = (x - 5)² + 64

Igualando teremos: x² - 10x + 25 + 64 = x² + 2x + 1 + 4
12x = 84----> x = 7

3° caso: BC = AC
72 = (x - 5)² + 64
(x - 5)² = 8
x = 5 + 2√2 ou 5 - 2√2
1 5 1